SEQUENCE OF STUDENTS’ ACTIVITIES IN TELLING TIME IN ENGLISH TEXTBOOK ENTITLED “WHEN ENGLISH RINGS A BELL" (PROJECT (Professional Journal of English Education), 2021)
Abstract The study aims to analyze the various sequences of students' activities in telling time. The book "When English Rings a Bell" is a book that researchers choose to specialize in research on time because time is the most important aspect for students to know in each activity. In analyzing data, researchers guide the (Bogdan & Biklen, 1997) descriptive methods of qualitative research as one of the procedures that produce descriptive data of the speech or written and attitudes of the observed ones. The researchers were also suggested in this study that children first read time and then soon after record time. The results of this study showed that by using this book students can sequence activities in telling time. Hour, half-hour, quarter-hour, five minute, and minute times in the sequence. And the teachers can teach students who have difficulty reading and recording analog and digital clocks. Keywords:  Analyze, Activities, Telling a Time